Plant-microorganism interactions in bioremediation of polychlorinated biphenyl-contaminated soil - Kurzawova, Veronika; Stursa, Petr; Uhlik, Ondrej; Norkova, Katarina; Strohalm, Martin; Lipov, Jan; Kochankova, Lucie; Mackova, Martina (New biotechnology, 2012)
During the second half of the last century a large amount of substances toxic for higher organisms was released to the environment. Physicochemical methods of pollutant removal are difficult and prohibitively expensive. Using biological systems such as microorganisms, plants, or consortia microorganisms-plants is easier, cheaper, and more environmentally friendly. The aim of this study was to isolate, characterize and identify microorganisms from contaminated soil and to find out the effect of plants on microbial diversity in the environment. Microorganisms were isolated by two approaches with the aim to find all cultivable species and those able to utilise biphenyl as a sole source of carbon and energy. The first approach was direct extraction and the second was isolation of bacteria after enrichment cultivation with biphenyl. Isolates were biochemically characterized by NEFERMtest 24 and then the composition of ribosomal proteins in bacterial cells was determined by MALDI-TOF mass spectrometry. Ribosomal proteins can be used as phylogenetic markers and thus MALDI-TOF MS can be exploited also for taxonomic identification because the constitution of ribosomal proteins in bacterial cells is specific for each bacterial species. Identification of microorganisms using this method is performed with the help of database Bruker Daltonics MALDI BioTyper. Isolated bacteria were analyzed from the point of the bphA gene presence. Bacteria with detected bphA gene were then taxonomically identified by 16S rRNA sequence. The ability of two different plant species, tobacco (Nicotiana tabacum) and nightshade (Solanum nigrum), to accumulate PCBs was studied as well. It was determined that various plant species differ in the PCBs accumulation from the contaminated soil. Also the content of PCBs in various plant tissues was compared. PCBs were detected in roots and aboveground biomass including leaves and berries.
Keywords: RNA, Ribosomal, 16S; látky znečišťující půdu; Ribosomal Proteins; Solanum; Bacteria; polychlorované bifenyly; Biodegradation, Environmental; biodegradace; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; ribozomální proteiny; Microbial Interactions; bakteriální geny; Soil Pollutants; Polychlorinated Biphenyls; tabák; RNA ribozomální 16S; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Genes, Bacterial; mikrobiální interakce; Nicotiana